2020
DOI: 10.14393/obv4n2.a2020-57485
|View full text |Cite
|
Sign up to set email alerts
|

Bases vigotskianas da Atividade Orientadora de Ensino

Abstract: O objetivo do artigo é discutir algumas bases vigotskianas que apoiam teórica e metodologicamente a Atividade Orientadora de Ensino. Para isso, inicialmente, o texto apresenta uma breve definição dessa Atividade. Em seguida, discorre sobre ideias vigotskianas como formação de conceitos e relação entre pensamento e fala. Como considerações finais, o artigo aponta a potencialidade educativa desse modo geral de organização do ensino.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Chemical abundance studies of individual clusters starting many decades ago began to demonstrate light element abundance inhomogeneities among red giant, horizontal branch, and even main-sequence (MS) stars (e.g., Popper 1947;Harding 1962;Cohen 1978) and modern studies have continued to reveal star-to-star abundance variations in an ever-growing number of GCs (see, e.g., references in the reviews by Gratton et al 2012;Bastian & Lardo 2018;Gratton et al 2019). Recent large-scale photometric studies have revealed color broadening and even splits in the giant branches and MSs of clusters, particularly when blue or ultraviolet (UV) filters are utilized (Piotto 2008;Lardo et al 2011;Monelli et al 2013;Lee 2015;Piotto et al 2015;Milone et al 2017;Bonatto et al 2019;Hartmann et al 2022). These color spreads are well correlated with the light element spreads found in spectroscopic studies (Marino et al 2008;Carretta et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical abundance studies of individual clusters starting many decades ago began to demonstrate light element abundance inhomogeneities among red giant, horizontal branch, and even main-sequence (MS) stars (e.g., Popper 1947;Harding 1962;Cohen 1978) and modern studies have continued to reveal star-to-star abundance variations in an ever-growing number of GCs (see, e.g., references in the reviews by Gratton et al 2012;Bastian & Lardo 2018;Gratton et al 2019). Recent large-scale photometric studies have revealed color broadening and even splits in the giant branches and MSs of clusters, particularly when blue or ultraviolet (UV) filters are utilized (Piotto 2008;Lardo et al 2011;Monelli et al 2013;Lee 2015;Piotto et al 2015;Milone et al 2017;Bonatto et al 2019;Hartmann et al 2022). These color spreads are well correlated with the light element spreads found in spectroscopic studies (Marino et al 2008;Carretta et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…É importante que ele leve diferentes formas de produções artísticas, mesmo que em fotografias ou vídeos, "possibilitando o enriquecimento do conhecimento estético" (ROSSI, 2003, p. 104). Na THC o professor é figura central na organização da atividade de ensino, de forma a mobilizar os estudantes para a apropriação dos conceitos por meio de uma atividade geradora de necessidade, pois foi ela, essa necessidade, que moveu o ser humano no seu processo histórico e agora permitirá aos alunos se apropriarem de tais conceitos e os modificarem (PIOTTO, 2020).…”
Section: )unclassified